2015
DOI: 10.1016/j.watres.2015.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and hydrologic variation of Bacteroidales, adenovirus and enterovirus in a semi-arid, wastewater effluent-impacted watershed

Abstract: Bacteroidales and viruses were contemporaneously measured during dry and wet weather conditions at a watershed-scale in a semi-arid watershed impacted by a mixture of agricultural runoff, municipal wastewater effluent and municipal runoff. The results highlight the presence of municipal wastewater effluent as a confounding factor for microbial source tracking (MST) studies, and thus data were segregated into groups based on whether they were impacted by wastewater effluent. In semi-arid environments such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Two of five storm outfalls were also positive for gull feces. Bambic et al (2015) reported the moderate occurrence of cattle and dog markers in stormwater samples ranging from 4.67 and 4.75 log 10 GC/L. Storm events led to an increase (4.67 and 4.75 log 10 GC/L) in cattle and dog feces-associated Bacteroides marker genes compared to dry events (3.23 and 3.20 log 10 GC/L).…”
Section: Marker Genes (Host)mentioning
confidence: 96%
See 1 more Smart Citation
“…Two of five storm outfalls were also positive for gull feces. Bambic et al (2015) reported the moderate occurrence of cattle and dog markers in stormwater samples ranging from 4.67 and 4.75 log 10 GC/L. Storm events led to an increase (4.67 and 4.75 log 10 GC/L) in cattle and dog feces-associated Bacteroides marker genes compared to dry events (3.23 and 3.20 log 10 GC/L).…”
Section: Marker Genes (Host)mentioning
confidence: 96%
“…In general, concentrations of pathogens in stormwater are poorly reported and some data may not be useful to infer risk or for quantitative microbial risk assessment (QMRA). For example, several studies have failed to detect or provided the percentage of samples positive for pathogens without giving quantitative numbers (Surbeck et al, 2006;Rajal et al, 2007;Sidhu et al, 2012a;Bambic et al, 2015). Most of the stormwater studies determined the concentrations of genus Cryptosporidium and Giardia.…”
Section: Pathogens In Stormwatermentioning
confidence: 99%
“…Human enteric viruses related to waterborne outbreaks could also be a concern in nutrient recovery from wastewater. , These viruses include noroviruses GI and GII (NoVs) and human adenoviruses (HAdVs), both associated with acute gastrointestinal infections in children and adults via environmental routes, , along with Enterovirus (EV) members, which can lead to various chronic diseases . While WWTPs may reduce viral loads to receiving environments, persistent virions such as noroviruses have been associated with spinach crop outbreaks from reclaimed wastewater uses .…”
Section: Introductionmentioning
confidence: 99%
“…32,33 These viruses include noroviruses GI and GII (NoVs) and human adenoviruses (HAdVs), both associated with acute gastrointestinal infections in children and adults via environmental routes, 34,35 along with Enterovirus (EV) members, 36 which can lead to various chronic diseases. 37 While WWTPs may reduce viral loads to receiving environments, persistent virions 38−40 such as noroviruses have been associated with spinach crop outbreaks from reclaimed wastewater uses. 41 Furthermore, analysis of a human virus surrogate (somatic bacteriophage ϕX174) in struvite recovered from urine shows that inactivation and infectivity can be affected by moisture content.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recreational water illnesses occur by exposure to contaminated waters in lakes, streams, pools, and oceans through activities such as fishing, swimming, or boating (Colford et al, 2007). These water bodies are vulnerable to contamination with pathogens from a variety of sources that can include septic tank malfunctions, the introduction of wastewater, storm drain contamination, and fecal discharge from animals and humans directly into the water (Withers et al, 2014;Bambic et al, 2015). Upon contact with contaminated recreational waters, children are at greater risk of gastroenteritis (Oh et al, 2003;Jones et al, 2014;Kotwal and Cannon, 2014).…”
Section: Introductionmentioning
confidence: 99%